Características generales de las revistas científicas peruanas - Santillan-Aldana, Julio (2017)
This paper presents for the first time an overview of the state of current Peruvian journals. After retrieving and filtering records from LATINDEX, 138 journals were identified and characterized by the following variables: geographical origin, publisher, frequency, format (print, electronic, or both), and subject. The results show that Peruvian journals are mostly published in Lima (66.7%) by a university (73.9%), come out every six months (56.5%) both in print and electronically (67.4%), and publish articles mainly about natural sciences (35.5%). The article points out some problematic issues as well as certain measures for improving the Peruvian journal publishing market.